АКАДЕМИК ЛИЦЕЙ-УНИВЕРСИТЕТ ТИЗИМИДА АНАЛИЗ АСОСЛАРИНИ ЎҚИТИШДА КОМПЛЕКС МЕТОД ВА УНИНГ УЗВИЙЛИКНИ ТАЪМИНЛАШДАГИ АҲАМИЯТИ - Алламбергенов, И.; Нурымова, Н. (SCIENCE and SOCIETY, 2019)
The article deals with the teaching succession of the basis of mathematical analysis using complex methods in the system of academic lyceum-university.
Keywords: shaped marks; shaped signs; coordination of imagination; educational information; translation of information from one language to another